Learning to Innovate: The Role of Ambidexterity, Standard, and Decision Process - Maggie Qiuzhu Mei (Copenhagen Business School (CBS), 2014)
Innovation is the engine of sustained organizational performance and is central to organizations' competitive advantage. In an effort to understand how to foster innovation at firms, extant research has highlighted the role of organizational learning in shaping innovation capabilities at firms. Motivated by the importance of innovation, this PhD dissertation aims to improve our understanding of the complex relationship between organizational learning and innovation capabilities at firms. The dissertation consists of three studies using various datasets and methodologies that investigate the relationship between organizational learning and innovation creation in an organizational context. Taking a nuanced view of organizational learning, the dissertation investigates how three different organizational learning processes could affect innovation creation at the firm level and project level. Specifically, essay 1 focuses on how to manage ambidextrous learning for superior radical and incremental innovation capabilities; essay 2 examines how learning through knowledge sharing in the context of standard setting impacts on firms' innovation performance; and essay 3 moves down to project level and explores how and when strategic decision comprehensiveness can affect new product development performance. Taken together, though examining three separate approaches that firms employ to manage organizational learning for innovation creation, the three studies in this dissertation collectively contribute to the understanding of managing organizational learning for innovation creation at firms. The three studies in this dissertation show how three prominent organizational learning processes impact on firms' innovation performance. Furthermore, the studies in this dissertation emphasize that there are limitation and boundary conditions for different organizational learning processes.
hdl:10398/8898
Keywords: 650